2 Ballinger’s Annotated Codes and Statutes of Washington: Showing All Statutes in Force, Including the Session Laws of 1897, at 1956, §§ 7082-7083 (1897) - (:unkn) unknown (General Publisher, 1897)
7082: Every person who shall, in a manner likely to cause terror to the people, exhibit or flourish, in the streets of an incorporated cit or an unincorporated town, any dangerous weapon shall be guilty of a misdemeanor[.] 7083: Every person who shall, in a rude, angry, or threatening manner, in a crowd of two. or more persons, exhibit any pistol, bowie knife, or other dangeous weapon, shall, on conviction, be senteced to imprisonment not exceeding one year and a fine of less than $500.
--
Keywords: BRANDISHING